Analysis of Macroeconomic Determinants and Forecasting of Indonesia’s Pulp Exports to China for the Period 2005–2030 - Muh Arief Syam; Bramasto Nugroho (Fakultas Kehutanan, Universitas Hasanuddin, 2026)
Indonesia's pulp exports rely heavily on the Chinese market, which underwent structural changes due to waste import bans. This study analyzes the effects of China's GDP, international pulp prices, and exchange rates on Indonesia's pulp export value (HS 4703) to China (2005-2024) and forecasts trends through 2030. Using Log-Log multiple linear regression and ARIMA methods, the results show that China's GDP, pulp prices, and exchange rates have positive and significant effects on export values. The inelastic nature of these variables indicates pulp is an essential, hard-to-substitute industrial material. The ARIMA(0,1,0) with drift model projects a stable increase in exports from USD 1.9 billion in 2025 to USD 2.3 billion in 2030. The study recommends that stakeholders ensure sustainable raw material supply through Industrial Plantation Forests (HTI) to meet this long-term demand growth.